Identifying the Value of Traditional Cultural Landscape in Rural Settlements - Tırnakçı, Aslıhan (Journal of History Culture and Art Research, 2021)
The traditions, socio-economic conditions, habitational settings and the climatic factors of a society become stratified with the cultural values ​​and establish the current values of the cultural landscape. The significance of a rural landscape as cultural heritage is directly related to the existence of cultural values and cultural landscape, which constitutes the totality of the cultural values ​​should be preserved in order to ensure historical and cultural sustainability. The study area (Şavşat/Artvin, Turkey) has a rich value based on its cultural landscape and texture, given its rich biodiversity and the lifestyle of different cultures that shaped the traditional settlement. Certain routes were determined within the scope of the present study, with the aim to encompass the whole Şavşat. A method based on an inventory study was employed to analyze the 39 rural settlements and the values of the traditional cultural landscape ​​were quantified through scoring 8 parameters based on the existence or nonexistence of cultural values. The 5-point scoring was ranged as follows: very low, low, medium, high and very high. Based on this scoring, Yavuz village, Kocabey, Kirazlı, Kayadibi, Çoraklı, Şavşat Center, Ilıca, Maden were found have high, Cevizli, Maden, Köprülü and Çağlayan were found to have very high values for the cultural landscape. Consequently, it was indicated that identifying the values of the traditional cultural landscape through the scoring system based on the existence and nonexistence of cultural values with respect to certain parameters could contribute to the literature. It was considered that the findings of the present study could provide an important database in the regional/sub-regional scale for the conservation of cultural values with natural landscape resources and conveying these values to future generations.